Cardiac Baroreflex Variability and Resetting during Sustained Mild Effort - Zamir, Mair; Badrov, Mark B.; Olver, T. Dylan; Shoemaker, J. Kevin (Frontiers in Physiology, 2017)
This exploratory study assessed the pattern of closed-loop baroreflex resetting using multi-logistic-curve analysis. Operating point gain and ranges of RR-interval (RRI) and systolic blood pressure (SBP) are derived to examine how these relate to sympathetic activation. Sustained low-intensity isometric handgrip exercise, with a period of post-exercise circulatory occlusion (PECO) provided a model to study baroreflex resetting because the progression towards fatigue at constant tension induces a continuous increase in volitional contribution to neuro-cardiovascular control. Continuous measurements of muscle sympathetic nerve activity (MSNA), blood pressure, and RRI were made simultaneously throughout the experimental session. Spontaneous sequence analysis was used to detect episodes of baroreflex “engagements”, but the results are examined with a view to the fundamental difference between experimental conditions that isolate the carotid sinus (open-loop) and intact physiological conditions (closed-loop). While baroreflex function under open-loop conditions can be described in terms of a single logistic curve, intact physiologic conditions require a family of logistic curves. The results suggest that the baroreflex is in a “floating” state whereby it is continuously resetting during the timeline of the experiment but with minute-by-minute average values that mimic the less complex step-wise resetting pattern reported under open-loop conditions. Furthermore, the results indicate that baroreflex function and resetting of the operating point gain is reflected not in terms of change in the values of blood pressure or RR-interval but in terms of change in the range of values of these variables prevailing under different experimental conditions.